Outcome of percutaneous mesh fixation in transabdominal preperitoneal groin hernia repair - Ahmed M Hegab (Wolters Kluwer Medknow Publications, 2021)
Background One of the commonly performed surgical procedures in general surgical practice is groin hernia repair. Different procedures have been prescribed for hernioplasty either by open or laparoscopic approaches. Tension-free hernioplasty and obliteration of myopectineal orifices necessitate mesh insertion with different methods for its fixation. Chronic groin pain post hernioplasty (either open or laparoscopic) has been considered multifactorial and most of it has been attributed to the method of mesh fixation. Aim This study aims to evaluate the outcome of temporary percutaneous mesh fixation in transabdominal preperitoneal repair (TAPP) using a fascial closure device or straight needle suture. Patients and methods This prospective study was carried out in the Department of General Surgery Al-Hussein Hospital, Al-Azhar University, Cairo, from October 2016 to December 2017, during which 30 patients were subjected to laparoscopic TAPP hernioplasty with percutaneous mesh fixation and followed up for 1 year. A full preoperative assessment was carried out on all patients. TAPP hernioplasty with percutaneous mesh fixation was performed for all patients; postoperative follow-up was performed for detection of early and late postoperative complications. All cases were followed up for 1 year to detect late complications such as chronic pain and recurrence. Results In this study, the mean age of the patients was 39.2 years. The operative time ranged from 50 to 90 min. All patients underwent uneventful TAPP repair for groin hernia; only one patient had port site bleeding, which was properly controlled during surgery. All patients were discharged on the second postoperative day with a mean hospital stay of 1 day and allowed to resume daily activities at mean 7.5 days postoperatively. Pseudohernia developed in 10% of patients without true recurrence. Only one patient developed recurrence 6 months postoperatively. One year postoperatively, none of the patients had persistent pain and there was no other recurrence. Conclusion Temporary percutaneous mesh fixation in TAPP hernioplasty either by fascial closure device or by straight needle suture is sufficient, effective in mesh fixation and reasonable in terms of cost, enabling better availability to all patients, and yielding nearly the same recurrence rate as ordinary TAPP without permanent groin pain.